Probing the tumorigenic potential of genetic interactions reconstituted in murine fallopian tube organoids. Issue 2 (21st July 2021) - Maru, Yoshiaki; Tanaka, Naotake; Tatsumi, Yasutoshi; Nakamura, Yuki; Yao, Ryoji; Noda, Tetsuo; Itami, Makiko; Hippo, Yoshitaka
Abstract: Genetically engineered mice have been the gold standard in modeling tumor development. Recent studies have demonstrated that genetically engineered organoids can develop subcutaneous tumors in immunocompromised mice, at least for organs that prefer predominant driver mutations for tumorigenesis. To further substantiate this concept, the fallopian tube (FT), a major cell of origin of ovarian high‐grade serous carcinoma (HGSC), which almost invariably carries TP53 mutations, was investigated for p53 inactivation‐driven tumorigenesis. Murine FT organoids subjected to lentiviral Cre ‐mediated Trp53 deletion did not develop tumors. However, subsequent suppression of Pten and simultaneous induction of mutant Pik3ca led to the development of carcinoma in situ and HGSC‐like tumors, respectively, whereas concurrent deletion of Apc resulted in the development of benign cysts, mirroring frequent activation of the PI3K/AKT axis and the marginal impact of Wnt pathway activation in HGSC. Consistent with the frequent activation of the RAS pathway in HGSC, mutant Kras cooperated with Trp53 deletion for the development of tumors, which unexpectedly contained sarcoma cells in addition to carcinoma cells, despite the epithelial origin of the inoculated organoids. This finding is in sharp contrast with the exclusive adenocarcinoma development from gastrointestinal organoids with the same genotype reported in previous studies, suggesting a tissue‐specific epithelial–mesenchymal transition program. In tumor‐derived organoids, the Cre ‐mediated recombination rate reached 100% for Trp53 but not for the other genes, highlighting the advantage of p53 inactivation in FT tumorigenesis. The Trp53 wildtype FT organoids expressing the mutant Kras developed sarcoma and carcinoma upon Cdkn2a suppression and Tgfbr2 deletion, respectively, revealing novel pro‐tumorigenic genetic cooperation and critical roles of TGF‐β signaling for epithelial–mesenchymal transition in FT‐derived tumorigenesis. Collectively, the organoid‐based approach represents a shortcut to tumorigenesis and provides novel insights into the relationships among genotype, cell type, and tumor phenotype underlying tumorigenesis. © 2021 The Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.